Greece's New Geopolitics - Lesser, Ian O. (RAND Corporation, 2001)
Greece has been profoundly affected by recent changes in the internationalenvironment, on its borders, and within the country itself. Manylong-standing assumptions about Greek interests and Greece_s role havefallen away and have been supplanted by new approaches. The country hasbecome progressively more modern and more European, and its internationalpolicy has become more sophisticated. At the same time, the geopoliticalscene has evolved in ways that present new challenges and new opportunitiesfor Athens in its relations with Europe, the United States, and neighboringcountries. Many of these challenges cross traditional regional boundariesand underscore Greece_s potential to play a transregional role, lookingoutward from Europe to the Mediterranean, Eurasia, and the Middle East. Thisreport explores the new geopolitical environment Greece faces, payingspecial attention to the implications for southeastern Europe andtransatlantic relations; explores options for Greek strategy; and offerssome new directions for policy in Greece and on both sides of the Atlantic.